Identification of Bacteria and Their Sensitivity Pattern From Corneal Ulcer Patients (Journal of Chittagong Medical College Teachers' Association, 2012)
Corneal ulcer is one of the major causes of blindness in Bangladesh. A total of 280 samples (corneal scraping) of different age groups were examined by microscopy and culture. Microorganism (bacteria & fungus) were recovered form 187 (66.78%) cases. Among these bacteria was recovered in 75 (26.76%) cases. Pseudomonas spp. was the most common 27 (36.00%) bacteria isolated. The next common bacteria was Streptococcus pneumonia 24 (32.09%) followed by Viridans Streptococcus 8 (10.67%), Staphylococcus aureus 6 (8%) Coagulase negative Staphylococcus 6 (8%), Escherichia coli 2 (2.66%), Corynebacterium spp 1 (1.33%) and Klebsiella spp 1 (1.33%). The antibiotic sensitivity pattern of bacterial isolates were found to be variable. Most of the Gram positive bacteria were sensitive to Penicillin, Choloramphenicol, Ciprofloxacin. The Gram negative bacteria were sensitive to Aminoglycosides. Quinolones were found to be most effective drug against majority of the Gram positive and Gram negative bacteria.JCMCTA 2011; 22(2): 32-36